2016
DOI: 10.1039/c6ta01098a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid capped carbon dots as a high-performance friction-reducing and antiwear additive for poly(ethylene glycol)

Abstract: This work presents ionic liquid capped carbon dots as a high-performance friction-reducing and antiwear additive for poly(ethylene glycol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(59 citation statements)
references
References 40 publications
0
59
0
Order By: Relevance
“…However, Wang et al [55] have already reported their application in tribology in combination with ILs. Carbon nanodots capped by an IL have been synthesized and dispersed in polyethyleneglycol.…”
Section: Ionanocarbon Lubricantsmentioning
confidence: 99%
“…However, Wang et al [55] have already reported their application in tribology in combination with ILs. Carbon nanodots capped by an IL have been synthesized and dispersed in polyethyleneglycol.…”
Section: Ionanocarbon Lubricantsmentioning
confidence: 99%
“…Ma et al [28] fabricated novel CQD and IL nanoparticles and discovered that the tribological behavior of these nanoparticles affects the lubrication of PEG, similar to the results found by Zhang [27]. Wang et al [29] used a one-pot pyrolysis method to synthesize IL (1-aminopropyl-3methylimidazolium bromide)-capped carbon dot particles. They indicated that the friction and wear mechanisms of composite particles involve the rolling, mending, and polishing of composite particles under friction, resulting in outstanding tribological behaviors in PEG.…”
Section: Introductionmentioning
confidence: 70%
“…15,16 After adding a relatively low concentration of CDs, the friction coefficient and wear volume can be effectively reduced compared with pure PEG. [15][16][17][18] Although there have been many studies on CDs in recent years, the specific structure of CDs have not been revealed yet. The core-shell structure is currently a generally accepted theory that under high temperature and high pressure, some precursors will remain on the surface of CDs instead of being carbonized, which allows CDs to retain the properties of the precursor.…”
Section: Introductionmentioning
confidence: 99%